Characterization of bulk hexagonal boron nitride single crystals grown by the metal flux technique - Edgar, James H.; Hoffman, Timothy B.; Clubine, B.; Currie, M.; Du, X.Z.; Lin, J.Y.; Jiang, H.X. (My University, 2014)
The optical and physical properties of hexagonal boron nitride single crystals grown from a molten metal solution are reported. The hBN crystals were grown by precipitation from a nickel-chromium flux with a boron nitride source, by slowly cooling from 1500 °C at 2-4°C/h under a nitrogen flow at atmospheric pressure. The hBN crystals formed on the surface of the flux with an apparent crystal size up to 1 to 2 mm in diameter. Individual grains were as large as 100-200 µm across. Typically, the flakes removed from the metal were 6 to 20 µm thick. Optical absorption measurements suggest a bandgap of 5.8 eV by neglecting the binding energy of excitons in hBN. The highest energy photoluminescence peak was at 5.75 eV at room temperature. The hBN crystals typically had a pit density of 5 x 10⁶ cm⁻² after etching in a molten eutectic mixture of potassium hydroxide and sodium hydroxide. The quality of these crystals suggests they are suitable as substrates for two dimensional materials such as graphene and gallium nitride based devices.
Keywords: Optical absorption; Photoluminescence; Hexagonal boron nitride; hBN; Single crystals